Towards Reverse Vaccinology for Bovine TB: High Throughput Expression of Full Length Recombinant Mycobacterium bovis Proteins - Paliwal, Deepa; Thom, Michelle; Hussein, Areej; Ravishankar, Divyashree; Wilkes, Alex; Charleston, Bryan; Jones, Ian M. (Frontiers in Molecular Biosciences, 2022)
Bovine tuberculosis (bTB), caused by Mycobacterium bovis, is a significant global pathogen causing economic loss in livestock and zoonotic TB in man. Several vaccine approaches are in development including reverse vaccinology which uses an unbiased approach to select open reading frames (ORF) of potential vaccine candidates, produce them as recombinant proteins and assesses their immunogenicity by direct immunization. To assess the feasibility of this approach we have cloned and expressed 124 ORFs from the M. bovis genome, using a mixture of E. coli and insect cell expression. We used a concatenated ORF design to reduce the number of clones required and single chain fusion proteins for protein pairs known to interact, such as the members of the PPE-PE family. Over 60% of clones showed soluble expression in one or the other host and most allowed rapid purification of the tagged bTB protein from the host cell background. The range of recombinant proteins produced represents a resource that is suitable for test immunisations as part of the development of an effective bTB vaccine.